Benefits of Soybean Pulp and Brown Rice Flour for Improving Carcass Performance and Reducing Fat Content in Peking Duck - Ayuti, Siti Rani; Mudastsir, Mudastsir; Delima, Mira Sukma; Ferasyi, Teuku Reza; Akmal, Muslim; Qomariyah, Novia; Andriani, Mira; Sadarman, Sadarman; Amalo, Filphin Adolfin; Subagyo, Djoko (Jurnal Agripet, 2025)
Soybean pulp and brown rice flour have a high protein content to increase the nutrients of Pekingese duck feed. The experimental research method used a Factorial Design with 5 treatments and 5 replicates, the details of the treatment were as follows: Control (a0r0), addition of brown rice flour (a1, a2, a3 and a4), and soybean pulp (r1, r2, r3 and r4). Soybean pulp 3-12% and brown rice flour 4-16% respectively. The parameters observed were feed consumption, live weight, feed conversion, carcass weight, carcass percentage, abdominal fat percentage, and meat fat content. The data obtained were processed according to the complete random design diversity analysis. Duncan's Multiple Range Test tested the values of different parameters between treatments at a 95% confidence level. The results showed that the addition of 3-12% soybean meal and 4-16% brown rice flour did not have a significant effect (P0.05) on feed consumption, live weight, feed conversion, weight and carcass percentage, except for the percentage of abdominal fat and fat content of Peking ducks. The addition of 12% soybean meal and 16% brown rice flour (a4r4) was able to reduce the percentage of abdominal fat by 47.5% and the content of meat fat by 55.2% compared to the control. This study concludes that the addition of 12% (r4) soybean pulp and 16% (a4) brown rice flour per kg of feed can reduce the percentage of abdominal fat and fat content of Peking ducks.